Загальний вигляд узагальнено-оборотних операторiв у банахових просторах - Журавльов, В.П. (Нелінійні коливання, 2016)
Доказаны теоремы об общем виде обобщенно-обратимых операторов в банаховых пространствах, которые являются топологически нетеровыми, топологически фредгольмовыми. Эти теоремы обобщают известные теоремы С. М. Никольского об общем виде фредгольмовых операторов и Ф. В. Аткинсона об общем виде нетеровых операторов в функциональных пространствах. We prove theorems on a general form of generalized invertible operators on Banach spaces in the case where the operators are topologically Noetherian or topologically Fredholm. These theorems generalize the well-known theorems of S. M. Nikol’sky on a general form of a Fredholm operator and of F. V. Atkinson on a general form of a Noetherian operator on a function spaces.